A world fit for money laundering: the Atlantic alliance’s undermining of organized crime control - Young, Mary Alice (Trends in organized crime, 2021)
This is the untold history of how prominent civil servants in the UK tailored US-devised anti-money laundering (AML) policies in ways that suited the needs of Britain’s financial services industry. In the aftermath of these initial compromises in 1987, criminal money managers in both the US and the UK were able to continue to operate in an environment that easily allowed them to hide and use dirty money. The researchers analysed six months of previously unseen personal correspondence and documents exchanged between various actors in the UK Government during 1987. From this they conclude that the core of the current, global AML regime, was not the destruction of drug money laundering and banking secrecy, nor the ending of criminal financial enablers and with it hot money; rather it was the protection and leverage of national trading interests on both sides of the Atlantic. And the drive to protect these interests would see crime control laws made, amended and changed to cater for the interests of the US and UK banking and finance industries. The file had been classified as secret and held by the UK Treasury until it was released to the public in 2017 as an archive document transferred to The National Archives in accordance with The Public Records Act and the Freedom of Information Act.